THE IMPACT OF THE FINANCIAL PERFORMANCE OF ISLAMIC BANKS ON ECONOMIC GROWTH : (A PANEL DATA ANALYSIS) - Tahraoui, Asma; Aouar, Aicha (The journal of contemporary issues in business and government, 2024)
This study analyses the impact of the financial performance of Islamic banks on economic growth (GDP) in all of Saudi Arabia, United Arab Emirates, Kuwait, Qatar. For this purpose, it uses Panel data methodology for the period from 2014-2021. The estimation results show that the financial performance of Islamic finance through profitability had a significant positive impact on economic growth. the empirical investigation found that the CPI, which is the proxy variable for inflation is statistically significant and negative for economic growth consistent with the economic conception.